(untitled) (Research, Society and Development, 2020)
This research aimed to carry out the development and analysis of reliability to identify and record the notion of Chemical Kinetics of undergraduate and graduate students from the Chemistry Licentiate Degree. This is a quantitative research. In this regard, a Likert Scale Survey was devised containing 18 questions and the multiple-choice options ‘strongly disagree’, ‘somewhat disagree’, ‘neither agree nor disagree’, ‘somewhat agree’, ‘strongly agree’ to identify the level of agreement of the respondent with each statement. Those statements were developed taking into account surveys on Kinetics teaching and were theoretically validated by experts in the field. Subsequently, the semantic validation was performed with potential survey respondents so that they pointed out their understandings about the questions. Changes were made to the survey based on the experts’ suggestions. Accordingly, its final draft consisted of the initial structure, except for the readjustment of the conceptual part of some questions as well as for the exclusion of the multiple-choice option ‘neither agree nor disagree’. The survey was answered by 55 respondents, including undergraduate and graduate students from the Chemistry Licentiate Degree from eight Brazilian public institutions. In order to analyze the reliability of the respondents’ answers, Cronbach’s Alpha was applied. The reliability value of alpha for the entire instrument was 0.64. After purifying it, contemplating only 12 questions from thematic groups B and C, its reliability was 0,94, suggesting high reliability and that the instrument made up of those questions is reliable and has consistent measurements.